Can training programs or rather wage subsidies bring the unemployed back to work? A theoretical and empirical investigation for Germany - Renate Neubäumer (Institute for the Study of Labor (IZA), 2010)
Our paper investigates the relative effects of wage subsidies and further vocational training on the subsequent employment prospects of previously unemployed program participants. First, we outline a theoretical approach based on a firm's hiring decision. For the relative effectiveness of both labor market programs the assumption concerning the formation of human capital is crucial and leads to competing hypotheses for the medium and long term. On the assumption that wage subsidies have no effect on human capital they improve individuals' employment prospects less than training programs. Contrariwise, on the assumption that the formation of human capital on subsidized jobs equals that by formal training subsidization has the same employment effect as a training program. Second, we test the two hypotheses empirically, using a large administrative data set from Germany and statistical matching techniques. Our treatment groups consist of unemployed persons taking up subsidized employment or entering a further vocational training program, respectively, during March 2003. To exclude unemployment after program end we estimate the effect of keeping a subsidized job versus participating in training and taking up a job immediately afterwards. The results strongly support the latter of our competing hypotheses: Previously subsidized individuals and trained individuals who found a job immediately afterwards have the same employment rates. This leads to the conclusion that firms value training on a subsidized job as much as formal training programs.
Keywords: J68; J64; J65; 330; Evaluation of active labor market programs; training programs; wage subsidies; propensity score matching; Arbeitsmarktpolitik; Weiterbildung; Berufsbildung; Lohnsubvention; Wirkungsanalyse; Arbeitsnachfrage; Personalbeschaffung; Theorie; Deutschland